황색포도상구균에 감염된 Keratinocyte 에서의 IL-1β 및 TNF-α 조절을 통한 액상 플라즈마의 상처 치유 촉진 - 양윤희 (The Graduate School, Ajou University, 2024)
배경 및 목적: 액상 플라즈마(Liquid Plasma)는 항균, 항염증, 조직 재생 등의 특성으로 인해 유망한 치료제로 부상하고 있으며, 최근 피부 관련 분야에서 많은 관심을 받고 있다. 상처 치료제는 박테리아를 효과적으로 제거하면서 숙주 피부 세포에 부정적인 영향을 최소화하는 것이 최적이지만, 시중에 판매하는 제품들은 박테리아뿐만 아니라 세포에도 독성을 유발하여 부작용이 나타난다. 그러므로, 세포의 독성을 최소화하는 치료제가 시급히 필요하다. 한편, 액상 플라즈마는 인체에 무해한 농도에서도 살균 효과를 나타났으며, 이전 연구에서 액상 플라즈마가 상처 치유에도 효과적이라는 것이 입증되었다. 따라서, 본 연구에서는 피부의 박테리아 감염 상태에서 액상 플라즈마가 감염 관리와 상처 치유를 동시에 해결할 수 있는지 확인하고, 그 메커니즘을 연구하는 것을 목표로 한다. _x000D_ 재료 및 방법: 세포실험에는 염증 반응에 관여하고, 궁극적으로 손상된 부위를 닫을 수 있는 각질세포의 특성을 모사하기 위해 인간 Keratinocyte인 HaCaT I 세포를 사용하였다. HaCaT 세포에 액상 플라즈마의 2.5, 5, 10, 20μM 농도를 처리하여 세포 사멸 분석 (MTT assay, Annexin V-PI staining assay, Western blot analysis)을 하였다. 황색포도상구균(Staphylococcus aureus)에 대한 액상 플라즈마의 항균, 항바이오필름 효과를 확인하기 위해 Antibacterial activity assay와 Biofilm formation assay를 진행하였다. S.aureus로 HaCaT 세포를 자극한 다음 염증 유전자 발현을 비교하기 위해 qPCR과 ELISA를 통해 확인하였고, 세포 상처치유 실험(cell scratch assay)을 진행하였다. _x000D_ 결 과: 액상 플라즈마는 HaCaT 세포의 세포사멸 변화에 영향 없음을 MTT assay 를 통해 관찰되었다. 하지만, 농도 범위의 최소 농도 액상 플라즈마를 처리했을 때, S.aureus 의 콜로니가 현저히 억제되어 액상 플라즈마의 강력한 항균 활성을 확인하였고, 형성된 바이오 필름에 액상 플라즈마 20 μM 를 처리했을 때에는 바이오필름 제거 능력을 관찰하였다. 한편, S. aureus 를 HaCaT세포에 처리했을 때, IL-1β와TNF-α발현이 유도되고 세포이동이 억제된다. 하지만, 액상 플라즈마를 함께 처리하면 두 단백질의 발현이 현저하게 감소하고, HaCaT 세포의 세포 이동이 회복되는 것을 관찰하였다. _x000D_ 결 론: 액상 플라즈마는 HaCaT 세포에 독성을 보이지 않으며, S.aureus에 대한 항균, 항바이오필름 효능이 있고, 박테리아 감염 상태에서 항염증 효과, 상처 회복을 향상시킬 수 있는 가능성을 in vitro 실험을 통해 증명하였으며, 이러한 효과들은 액상 플라즈마가 다양한 형태의 상처를 치료하는데 유익할 수 있음을 보여준다.|Backgrounds and Objectives: Liquid plasma is emerging as a promising therapeutic agent due to its antibacterial, anti inflammatory, and tissue regeneration properties, and has recently garnered significant attention in the field of dermatology. The wound healing agent effectively eliminate bacteria while minimizing negative effects on host skin cells. However, commercially available products induce toxicity not only in bacteria but also in cells, leading to side effects. Therefore, there is an urgent need for a wound healing agent that minimizes cellular toxicity. On the other hand, liquid plasma has shown antimicrobial effects even at concentrations harmless to the human body, and previous studies have demonstrated its effectiveness in wound healing. Therefore, in this study, we aim to investigate the ability of liquid plasma to ３２ simultaneously manage infection and promote wound healing in bacterial skin infections and elucidate its underlying mechanisms. _x000D_ Materials and Methods: HaCaT cells were used to mimic the characteristics of human keratinocytes, which are involved in the inflammatory response and ultimately close the damaged area. HaCaT cells were treated with liquid plasma at concentrations of 2.5, 5, 10, and 20 µM, and cell viability analysis (MTT assay, Annexin V PI staining assay, Western blot analysis) was performed. To assess the antibacterial and antibiofilm effects of liquid plasma against Staphylococcus aureus, an antibacterial activity assay and a biofilm formation assay were conducted. After stimulating HaCaT cells with S.aureus, the expression of inflammatory genes was compared using qPCR and ELISA, and a cell scratch assay was performed. _x000D_ Results: Liquid plasma shows no cytotoxicity to HaCaT cells, as observed through the MTT assay. However, when treated with the minimum concentration range of liquid plasma, there was a significant inhibition of S. aureus colonies, demonstrating the potent antibacterial activity of liquid plasma. Furthermore, when 20 µM of Liquid plasma was applied to the formed biofilm, its biofilm removal capability was observed. Additionally, when S. aureus was treated with HaCaT cells, it induced the expression of IL-1β and TNF-α and inhibited cell migration. However, co-treatment with liquid plasma markedly ３３ reduced the expression of these proteins and restored HaCaT cell migration. _x000D_ Conclusion: These in vitro experiments demonstrate that liquid plasma is non-toxic to HaCaT cells, possesses antibacterial and antibiofilm efficacy against S. aureus, and has anti-inflammatory effects and wound healing potential in the context of bacterial infection. These findings suggest that liquid plasma could be beneficial in treating various types of wounds.
학위논문(석사)--의생명과학과,2024. 8
Keywords: Cell migration; Inflammation; Liquid plasma; Staphylococcus aureus; Wound healing